A magnetostatic force inspection method for monitoring the oscillation marks of continuous casting. (25th September 2015) - Chen, Xinyue; Wang, Xiaodong; Ren, Zhongming; Tao, Zhen; Na, Xianzhao; Wang, Engang
Abstract: Based on the well-known fact that ferromagnetic materials can be significantly attracted by a permanent magnet (PM), we develop an innovative magnetostatic force inspection method to monitor the oscillating marks formed during continuous casting. A small PM produces a static magnetic field that penetrates into the ferromagnetic material slab formed via continuous casting. This magnet forms a localized magnetic sensing zone (MSZ) within the ferromagnetic material. The magnetostatic force acting on the ferromagnetic material can be expressed as the Maxwell tensor integral over the surface of the ferromagnetic material within the MSZ. This force provides local surface profile information. The reaction force of the magnetostatic force acting on the PM can be measured using a laser–cantilever system (a high force resolution method), and thus the profile features of the oscillation marks can be obtained. A measuring device with a laser–cantilever system is designed, constructed, and applied in a series of prototypes and a static experiment. A numerical model is simultaneously constructed to validate the measurement results. The differences between the actual and measured profiles are analyzed. An actual steel specimen with oscillation marks is measured using this device, and the accuracy is evaluated. In summary, the potential for the application of this method in the metallurgy industry is demonstrated.